Latin America in the Twentieth Century - Calvert, Peter. author. aut Link
XI, 240 p.
Keywords: Latin America has long had a reputation for violence and unpredictability. In this study, two specialists in Latin American politics present a new view of this vital region, its frustrations, setbacks and its exciting possibilities.